Anatomy of the Tarsal Canal and Sinus in Relation to the Subtalar Joint Capsule. (November 2018) - Yamaguchi, Reiko; Nimura, Akimoto; Amaha, Kentaro; Yamaguchi, Kumiko; Segawa, Yuko; Okawa, Atsushi; Akita, Keiichi
Background: Anatomical knowledge of the tarsal canal and sinus is still unclear owing to the complexity of the ligamentous structures within them, particularly the relationship with the capsules of the subtalar joints. The aim of this study was to examine the anatomical relationship between the fibrous tissues of the tarsal canal and sinus and the articular capsules of the subtalar joint. Methods: We conducted a descriptive anatomical study of 21 embalmed cadaveric ankles. For a macroscopic overview of the subtalar joint, we removed the talus in 18 ankles and separated the fibrous tissues from the surrounding connective tissues to analyze the layered relationship between the inferior extensor retinaculum (IER) and the subtalar joint capsule. Additionally, we histologically analyzed the tarsal canal and the medial and lateral sides of the tarsal sinus using Masson's trichrome staining in 3 ankles. Results: The medial and intermediate roots of the IER and interosseous talocalcaneal ligament (ITCL) were located in the same layer and were connected to each other, between the capsules of the posterior talocalcaneal and talocalcaneonavicular joints. The intermediate root of the IER and the cervical ligament (CL) had adjacent attachments on the tarsal sinus, and synovial tissues originating from the joint capsules filled the remaining area in the tarsal canal and sinus. Conclusion: We determined that the tarsal canal and sinus tarsi contained 3 layered structures: the anterior capsule of the posterior talocalcaneal joint, including the anterior capsule ligament; the layer of ITCL and IER; and the posterior capsule of the talocalcaneonavicular joint, including the CL. Clinical Relevance: The results of this study may help with the understanding of the pathomechanism of subtalar instability and sinus tarsi syndrome, resulting in better treatment.